Crawlers on the Seabed – The Famous Devonian Trilobites of Gerolstein - Jens Koppka (Geoconservation Research)
This paper introduces the Middle Devonian trilobites of Gerolstein, found on the famous trilobite fields of Gees and at the Auberg hill in Gerolstein. The research history and local geology of both sites are briefly discussed and key publications for further studies are provided. Owing to the early start of trilobite related research in the early 19th century, many trilobite taxa of high taxonomic value are described from the region, which later on became name-givers for higher taxa, e.g., families and even orders. The beautiful landscape and nature of Gerolstein, together with its rich geological and fossil heritage have been a magnet for early geotourism that started already in the 19th century and continues today. Guided or independent hiking, following the many hiking trails in the area, including the famous “Eifelsteig”, are the main attractions. Today, fossil collecting is not allowed in the area, but many fantastic fossil treasures including the famous Devonian trilobites and crinoids can be seen in the exhibitions of the Natural History Museum of Gerolstein. The museum has the task to preserve the geological and fossil heritage of the region. It provides guided tours through exhibitions and geological hikes in Gerolstein, and offers for children special geoeducational programs, tours and courses.